Non-invasive evaluation of electrical brain activity: effects of non-medicative treatment and subject’s state - Griškova-Bulanova, Inga (Acta medica Lituanica, 2013)
Introduction. The electroencephalogram (EEG) and evoked potentials (EPs) are widely used in psychiatry. Thus, it is important to standardize recording conditions according to instructions, arousal and attention levels of the subject. Also, it is important to evaluate the effect of nonpharmacologic treatment (electroconvulsive therapy (ECT) and transcranial magnetic stimulation (TMS)) on EEG and EPs. In this paper, an overview of researches, conducted in the above mentioned directions in Lithuania, is given. Materials and methods. EEG was recorded using standard protocols; P300, P50 and auditory steady-state responses (ASSR) were elicited. 44 schizophrenic patients, 25 depressive patients and 136 healthy subjects were investigated. Effects of ECT treatment, 10 Hz TMS procedure, and varying attention and arousal levels on EEG/EPs were investigated. Results. ECT had no negative impact on P300; alongside with clinical response, normalization of P300 parameters occurred. It was related to subject’s age and autonomic nervous system response during the treatment. A single 10 Hz TMS procedure produced a profound increase in the delta power of background EEG. In lower arousal level conditions, higher and more precise P50 potential, ASSR and background alpha power were observed. During distraction task performance, reduced gamma band response and ASSR, and increased background gamma power were observed. Conclusions. During the treatment course of ECT it is recommended to evaluate P300 potential changes and to monitor subject’s indices of the autonomic nervous system function, as these are related to clinical efficiency. Passively elicited auditory responses should be registered during low arousal unfocused attention conditions when the most precise responses of the highest amplitude are registered.
Keywords: electroencephalogram; evoked potentials; optimal recording conditions; electroconvulsive therapy; transcranial magnetic stimulation